If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4y + 9y + -7x = 0 Reorder the terms: 3x + -7x + -4y + 9y = 0 Combine like terms: 3x + -7x = -4x -4x + -4y + 9y = 0 Combine like terms: -4y + 9y = 5y -4x + 5y = 0 Solving -4x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. -4x + 5y + -5y = 0 + -5y Combine like terms: 5y + -5y = 0 -4x + 0 = 0 + -5y -4x = 0 + -5y Remove the zero: -4x = -5y Divide each side by '-4'. x = 1.25y Simplifying x = 1.25y
| y=0.6y | | 2/3(2x-9) | | 1-x=2x+1 | | X^2-5p-14=0 | | -7=t-8 | | 12x^2+12x+6=0 | | ln(x-3)+ln(x)=0 | | 1/2-4/3w=-1/5 | | 12x+9y=294 | | 8x-11v+17x+5v= | | 4x^4+x^2-3=0 | | 1/2-2/3w=-1/5 | | -3(4-2g)-6= | | 4x+3y-98=0 | | 3(x+3)=8x+8-5x+1 | | 2x+4y-30=180 | | -2(-5z)=60 | | 2x+4y-30=1890 | | 25=2000/12 | | 7.4-0.7y+2.6-0.9y=16-1.6y-4.4 | | 343-6x/36+1 | | x=85+-3.33y | | 2.9n=12.18 | | 3x^(2/3)-14x^(1/3)-5=0 | | 2t^2-10t+12=0 | | 18=-3(3z) | | (6p+x+2)+(3p-3x-5)= | | 5y-60+5y-60+3x+45=180 | | 19+5p+6p-14=14p+15-3p-10 | | 15x+22y=40 | | 18-8=x/3 | | 7x^(2/3)-13x^(1/3)-2=0 |